Contemporary problems of energy security of agriculture - Bolyssov, T.; Tyll, L. (BUKETOV BUSINESS REVIEW, 2019)
In the article the controversial questions of the nature and significance of management system of energy security are examined. The features of energy security classification levels are considered by following levels: nano-level, micro-level, meso-level, macro-level and mega-level. The authors of the article defined the place and role of agriculture in the structure of energy security. The article notes that the energy security of agriculture is associated with ensuring the progressive development of productive forces and improving the efficiency of production in the agricultural sector of the economy, as well as the creation of the necessary housing and social conditions in rural areas. The authors identified the main consumers of electric energy in rural areas: houses of workers and employees in settlements, farms; objects of social infrastructure; industrial consumers of farms; enterprises of agro-industrial complex, grain receiving points, enterprises for processing of agricultural products; other consumers. According to the authors, the electric load of rural areas is constantly changing, following the features of the structure of agricultural production and employment of the rural population, which are not constant, associated with both seasonality and employment during the day. In the article the factors influencing the energy security of agriculture are highlighted: socio-political factors; technogenic and natural factors; management and legal factors.